Time‐dependent model and life prediction for reinforcement corrosion in magnesium oxychloride cement concrete. (30th March 2020) - Gong, Wei; Wang, Nan; Zhang, Na; Chen, Guangfeng
Abstract: An effective approach to make better use of the salt‐brine resistance of magnesium oxychloride cement concrete (MOCC) and reduce "magnesium damage" (the concentrate of magnesium resources) that destroys the ecological balance in salt lake areas is to apply MOCC widely. However, the first problem is the high chloride ion content in MOCC, which corrodes reinforcement easily. Concrete cover depth, the experimental environment, and surface treatment of rebar were considered factors study in reinforcement corrosion in MOCC. Based on the tests conducted, a time‐dependent model for reinforcement corrosion in MOCC was proposed, and its life time (initial corrosion and initial cracking time) was calculated and verified in tests. The results showed that proper coating could inhibit reinforcement corrosion and increase the service life of rebar significantly. Further, the salt lake environment had little influence on reinforcement corrosion in MOCC. For exposed rebar in MOCC, the larger the concrete cover depth, the more serious the reinforcement corrosion, while, for coated rebar, the converse was true. All cases of reinforcement corrosion in MOCC conformed to the logarithmic‐type time‐dependent model before concrete cracking. Accordingly, reinforcement corrosion in MOCC and the excess of magnesium resources are expected to be solved.